Potential method in the coupled linear quasi-static theory of thermoelasticity for double porosity materials - Mikelashvili, M. (Archives of Mechanics, 2023)
This paper concerns the coupled linear quasi-static theory of thermoelasticity for materials with double porosity under local thermal equilibrium. The system of equations of this theory is based on the constitutive equations, Darcy’s law of the flow of a fluid through a porous medium, Fourier’s law of heat conduction, the equations of equilibrium, fluid mass conservation and heat transfer. By virtue of Green’s identity the uniqueness theorems for classical solutions of the internal and external quasi-static boundary value problems (BVPs) are proved. The fundamental solution of the system of steady vibration equations in the considered theory is constructed and its basic properties are established. Then, the surface and volume potentials are presented and their basic properties are given. Finally, on the basis of these results the existence theorems for classical solutions of the above mentioned BVPs are proved by means of the potential method (boundary integral equation method) and the theory of singular integral equations.